Multiple myeloma and cardiovascular risk (a literature review) - B. B. Samura; M. O. Panasenko; S. Ya. Dotsenko (Zaporozhye State Medical University, 2020)
Multiple myeloma is a plasma cell clonal malignancy that accounts for 10 % of hematological cancers. It predominantly affects elderly people; median age at diagnosis is 70 years. Consequently, many patients with MM have cardiovascular comorbidities or risk factors. MM can cause cardiac comorbidities such as cardiomyopathy and heart failure caused by cardiac amyloidosis and/or anemia. Heart dysfunction occuring after cytostatic drugs and monoclonal antibodies intake may act as a limiting factor in multiple myeloma treatment. Side effects of chemotherapy include hypotension, hypertension, arrhythmias, conduction disturbances, pericarditis, thromboembolic events, heart failure, death. Advances in pharmacotherapy for MM, such as the introduction of immunomodulators, proteasome inhibitors, and monoclonal antibodies, have dramatically improved life expectancy, but new agent classes are associated with adverse effects, including cardiovascular events. The risk of cardiotoxicity may be increased by some factors that include drug exposure, age, history of heart diseases, arterial hypertension, drug combination, previous radiotherapy or chemotherapy. However, with careful risk assessment, monitoring, and prophylactic therapy, many of these cardiovascular complications can be managed or treated successfully. It is important to detect cardiovascular toxicity before clinical signs of heart and vessel disturbance appear. The role of markers in elicitation of cardiovascular events risk group is still uncertain. Early definition of risk factors for prognosis of cardiovascular events appearing after polychemotherapy of multiple myeloma is an important and yet unsolved problem.